Perpetual Motion Dance, Digital Cultures, and the Common - Bench, Harmony (University of Minnesota Press, 2020)
A new exploration of how digital media assert the relevance of dance in a wired world How has the Internet changed dance? Dance performances can now be seen anywhere, can be looped endlessly at user whim, and can integrate crowds in unprecedented ways. Dance practices are evolving to explore these new possibilities. In Perpetual Motion, Harmony Bench argues that dance is a vital part of civil society and a means for building participation and community. She looks at how, after 9/11, it became a crucial way of recuperating the common character of public spaces. She explores how crowdsourcing dance contributes to the project of performing a common world, as well as the social relationships forged when we look at dance as a gift in the era of globalization. Throughout, she asks how dance brings people together in digital spaces and what dance's digital travels might mean for how we experience and express community. From original research on dance today to political economies of digital media to the philosophy of dance, Perpetual Motion provides an ambitious, invigorating look at a commonly shared practice.